PENERAPAN MODEL ANTRIAN PADA APOTEK PUSKESMAS INGIN JAYA KABUPATEN ACEH BESAR - Irawan, Heri Tri; Pamungkas, Iing; Muzakir, Muzakir (Universitas Teuku Umar, 2018)
The pharmacy is a place for the taking of drugs available at the Puskesmas Ingin Jaya, where in the process of taking drugs often there is a queue at certain times. This study aims to improve services so as to minimize the average waiting time for taking drugs while waiting in the queue and the service queue system so that the queue does not occur too long. The analytical method used is queuing theory analysis in accordance with the single phase single channel model or M / M / 1 which is applied to the pharmacy Puskesmas Ingin Jaya. The results of research on the process of taking drugs at the pharmacy Puskesmas Ingin Jaya by using queuing theory analysis, namely by calculating the queue model of one service line shows that in the non-rush hour condition, the number of facility lines used by one facility line is good, but not at the hour condition busy at 09.00-10.00, which shows that the longest patient waiting in the queue is 11 people, while the shortest queue is at 11.00-12.00, 9 people. The suggestion in this study is to add one service facility during the peak hour period, namely to become two facilities so that it is expected to optimize the performance of the service in the process of taking drugs.